A longitudinal study of the efficacy of lean learning experienced through a simulated working environment (SWE). Issue 5 (12th June 2017) - van der Merwe, Karl R.
Abstract : Purpose: The purpose of this paper is to determine the efficacy of lean learning as experienced and demonstrated by a group of students who were exposed to a purpose built simulated working environment (SWE). The study expands on previous research aimed at establishing the student views of the new type of training by including the perceptions of the industry mentors. Design/methodology/approach: An SWE was developed to allow students to experience an assembly line environment and practice lean tools. The students' perceptions of the learning process and the perceptions of their industry mentors were then measured to gauge the success of the programme. Findings: Groups of students indicated that they believed their grasp of the basic lean concepts had been significantly enhanced through exposure to the SWE teaching exercises. The outcome of this initial study was endorsed by the findings of the second study that measured the perceptions of their industry mentors after a six-month experiential learning period. Research limitations/implications: The research covered in this paper reflects only the findings of these two groups as they progressed from the SWE-type training to industry-based experiential learning. It is acknowledged that expanded research would be beneficial to not only verify initial findings but also to refine the lean learning experienced in the simulated work environment. Originality/value: The paper describes a lean learning process that is more effective than current processes and could therefore be universally utilised to enhance the lean learning experience in higher education.